How valid is the commercially available tennis match analysis mobile application? Is it good enough? - Choe, J.-P.; Hwang, I.-W.; Park, J.-H.; Amo, C.; Lee, J.-M. (International Journal of Performance Analysis in Sport, 2024)
The present study examines the validity of the SwingVision application by comparing SwingVision`s data to criterion data. Also, we investigated the difference in recording angles of SwingVision (optimal and suboptimal). Six college students played four matches, and every match was recorded from two different angles. After the data collection, recorded videos were analysed by SwingVision and human analysts (criterion). A total of 1065 strokes were analysed in the agreement of SwingVision and human analysts. Cross-tabulation with a column proportion test, Cochran`s Q test, and Kappa statistics were utilised to demonstrate the association of categorical variables (stroke, hit depth, hit zone, bounce depth, bounce zone, spin, result) between the three data (i.e. optimal, suboptimal, and criterion). Repeated measures analysis of variance (ANOVA) and Pearson correlation were used to compare speed data. SwingVision data in most variables showed high proportional similarity and percent agreement with criterion data. Additionally, the optimal angle data had much more similar results to the criterion data than the suboptimal data. Therefore, this present study documented that SwingVision is trustworthy, and users should be aware of possible errors derived from angle differences.